The genetic variability and evolution of red-spotted grouper nervous necrosis virus quasispecies can be associated with its virulence - Ortega-del-Campo, Sergio; Díaz-Martínez, Luis; Moreno, Patricia; García-Rosado, Esther; Alonso-Sánchez, María del Carmen; Béjar-Alvarado, Julia; Grande-Pérez, Ana (Frontiers, 2023)
El virus de la necrosis nerviosa (NNV) es un virus neurotrópico que causa la enfermedad viral de necrosis nerviosa en diversas especies de peces, incluido el lubina europea (Dicentrarchus labrax). Su genoma de RNA monocatenario positivo bisegmentado codifica la ARN polimerasa (RNA1) y la proteína de la cápside (RNA2). La especie más prevalente en lubina es RGNNV, responsable de alta mortalidad en larvas y juveniles. Estudios de genética reversa vinculan el aminoácido 270 de la cápside con la virulencia de RGNNV. NNV genera quasispecies y reasortantes que se adaptan a presiones selectivas como la respuesta inmune o el cambio de hospedador. En este estudio, lubinas fueron infectadas con dos virus recombinantes: rDl956 (alta virulencia) y Mut270Dl965 (baja virulencia). Se cuantificaron los segmentos virales en cerebro por RT-qPCR y se analizó la variabilidad genética por NGS. La carga viral de RNA1 y RNA2 en peces infectados con Mut270Dl965 fue 1,000 veces menor que en rDl956, y se observaron diferencias en la relación Ts/Tv, frecuencia de recombinación y heterogeneidad genética del RNA2. Esto indica que una sola mutación puntual puede alterar todo el quasispecies. En dorada (Sparus aurata), hospedador asintomático, rDl965 mostró carga viral y variabilidad genética similares a Mut270Dl965 en lubina, sugiriendo que la evolución y variabilidad genética del espectro de quasispecies de RGNNV se asocia con su virulencia.

Nervous necrosis virus (NNV) is a neurotropic virus causing viral nervous necrosis disease in various fish species, including European sea bass (Dicentrarchus labrax). Its bisegmented positive-sense RNA genome encodes the RNA polymerase (RNA1) and capsid protein (RNA2). The most prevalent species in sea bass is RGNNV, causing high mortality in larvae and juveniles. Reverse genetics studies link amino acid 270 of the capsid to RGNNV virulence. NNV generates quasispecies and reassortants capable of adapting to selective pressures like host immunity or host switching. In this study, sea bass were infected with two recombinant viruses: rDl956 (highly virulent) and Mut270Dl965 (low virulence). Viral genome segments were quantified in brains by RT-qPCR, and quasispecies variability was analyzed by NGS. RNA1 and RNA2 copies in Mut270Dl965-infected fish were 1,000-fold lower than in rDl956, with differences in Ts/Tv ratio, recombination frequency, and RNA2 mutant spectrum heterogeneity. This shows that a single point mutation can alter the entire quasispecies. In sea bream (Sparus aurata), an asymptomatic carrier, rDl965 displayed viral load and genetic variability similar to Mut270Dl965 in sea bass, suggesting that RGNNV quasispecies evolution and variability are associated with virulence.
Keywords: Acuicultura; Perciformes; NNV; NGS; Virulence; Quasispecies; Genetic variability; Haplotype reconstruction; Recombination; Comparative analysis